Patient Perspectives of a Non-Invasive Telemonitoring Tool for Patients with Heart Failure - Motohiro Sano PhD, RN; Sho Okada PhD, MD; Tomoko Majima PhD, RN; Yoshio Kobayashi PhD, MD (SAGE Publishing, 2022)
Aim Advancements in telemonitoring (TM) for patients with heart failure (HF) are incongruous because of the effect of TM intervention and various types of TM. This study aimed to clarify patients' experiences in using the TM tool. Methods This was a qualitative study. Data were evaluated using qualitative content analysis. Nine patients with heart failure → HF participated and completed the 1-month study period. Results The experience of this TM tool was determined using semi-structured interviews followed by qualitative content analysis. Finally, five themes emerged: habituation of self-care behaviour, no burden for use, a feeling of security, additional functions and advice rather than guidance. Conclusion This TM tool is easy to use and has the potential to promote self-management in patients with HF. Based on the aforementioned findings, we revised this tool and added some functions and will perform additional tests.